2004
DOI: 10.1080/09286580490514577
|View full text |Cite
|
Sign up to set email alerts
|

How reliable is the clinical exam in detecting ocular chlamydial infection?

Abstract: Despite modest inter-grader reliability and correlation with evidence of infection, the clinical exam is widely used due to its convenience and low cost. Efforts to make laboratory tests for ocular Chlamydia trachomatis more affordable would be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 15 publications
6
32
0
2
Order By: Relevance
“…Sixteen study villages were randomly selected from the Enemore district of the Gurage Zone, and received biannual treatment for two years (at months 0, 6,12,18). Eight study villages randomly selected from the adjacent district of Goro received biannual treatment for three years (at months 0, 6,12,18,24,30). During a mass treatment, all eligible members of the village were offered single dose, directly observed oral azithromycin (1 g for adults and 20 mg/kg for children ≥ 1 year of age).…”
Section: Introductionmentioning
confidence: 99%
“…Sixteen study villages were randomly selected from the Enemore district of the Gurage Zone, and received biannual treatment for two years (at months 0, 6,12,18). Eight study villages randomly selected from the adjacent district of Goro received biannual treatment for three years (at months 0, 6,12,18,24,30). During a mass treatment, all eligible members of the village were offered single dose, directly observed oral azithromycin (1 g for adults and 20 mg/kg for children ≥ 1 year of age).…”
Section: Introductionmentioning
confidence: 99%
“…y es el mecanismo más efectivo para controlar la enfermedad, pero el más difícil de implementar por la carencia de agua y por las costumbres, actitudes y cultura de las comunidades afectadas; E, mejoramiento ambiental (enviromental improvement), que abarca el suministro de agua y de vivienda adecuadas (1)(2)(3)(4)29). Diferentes evaluaciones de este programa han demostrado que produce un impacto significativo en el control del tracoma y de la ceguera (8)(9)(10)(11)(12). La meta de la OMS es eliminar la enfermedad para el año 2020 (11,29).…”
Section: Discussionunclassified
“…Se buscaron los signos cardinales del tracoma, pues los cambios que la enfermedad produce en el ojo tienen fases reconocibles clínicamente, que constituyen una forma aceptada de diagnóstico, con alta sensibilidad y que son (8)(9)(10)(11)(12) • Inflamación folicular por tracoma: presencia de cinco o más folículos en la conjuntiva del tarso de no menos de 0,5 mm.…”
Section: Comunidades Con Sospecha De Tracomaunclassified
“…It is possible to detect intracytoplasmic inclusions of Chlamydia by Giemsa staining, as well as using culture and sensitivity testing with the use of tissue culture [2]. Modern molecular methods, including fluorescent-labeled monoclonal antibodies and PCR, are available and may be more accurate [14]. However, some studies have shown that there is surprisingly poor correlation with clinical diagnosis, particularly in low-prevalence settings [14].…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%